Lewis and Bronsted multifunctionality: an unusual heterocycle from the reaction of bis(pentafluorophenyl)borinic acid with nitriles - Britovsek,GJP; Ugolotti,J; Hunt,P; White,AJP (Chem. Commun., 2006)
The combination of Lewis and Bronsted acidity as well as Lewis basicity in (CF)BOH results in a remarkable reactivity towards organonitriles to give novel heterocyclic compounds containing a BOBOCN six-membered ring.